Bahasa gipsi laut palau penelitian dini di Sabah - Saidatul Nornis Hj Mahali (ResearchGate, 2019)
The Bajau ethnic are known to be found at three neighbouring countries – Malaysia, Indonesia and Philippines. The Bajau is always perceived as an efficient diver and scary sea wanderer or sea traveler. In each country, they have different background history. Today, the Bajau are citizens of these three countries. Based on different geographical and cultural background, definitely this group which is known as Bajau has been influenced by the differences. Therefore, this paper will try to uncover the Bajau which inhabit Sabah. This paper will give attention to the language and cultural differences between the Bajau in Sabah and other Bajau in Nusantara in their effort to be accepted, socialized and adapted in every country.